HUBUNGAN PENDIDIKAN KARAKTER DENGAN KEARIFAN LOKAL - Muh. Nasrun (LPPM Universitas Muhammadiyah Bulukumba, 2022)
The design of this research is descriptive, the population in this study is class XI students of the Department of Computer and Network Engineering at SMK Muhammadiyah Bulukumba as many as 24 people using total sampling technique, that is, the entire population can be used as a sample, namely 24 people. Data Collection Techniques Are Documentation And Questionnaires Using Product Moment Correlation Data Analysis Techniques. Based on the results of the study with a significant level of 5 percent and N equals 24, it turns out that the limit for rejection of Ho in Table R is 0.333. R Count Equals 1.091 Turns out greater than From R Table equals 0.333 Means R Xy Count Value is Significant, So Ho is Rejected and H1 is Accepted It means that there is a relationship between character education and local wisdom at SMK Muhammadiyah Bulukumba.